Damage of high-strength reinforced concrete columns under horizontal and vertical loading - Bairrăo, Rogerio; Kačianauskas, Rimantas; Kliukas, Romualdas (Journal of Civil Engineering and Management, 2003)
The global damage of the high-strength reinforced concrete columns is investigated experimentally. Two identical specimens with annular cross-section and spiral containment were designed and two tests up to failure for the both specimens were carried out at the LNEC shaking table facilities. The columns worked as plane cantilever beams under the action of the constant vertical concentrated force and time-dependent concentrated horizontal force. The global damage concept is based on stiffness degradation. A variation of the observed horizontal displacements and forces during experiments as well as evolution of damage are presented and considered in details. The results show that increase of loading values is dominating factor of the global damage.First Published Online: 26 Jul 2012